Combinatorial Optimization and Applications 5th International Conference, COCOA 2011, Zhangjiajie, China, August 4-6, 2011. Proceedings - Wang, Weifan; Zhu, Xuding; Du, Ding-Zhu (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Combinatorial Optimization and Applications, COCOA 2011, held in Zhangjiajie, China, in August 2011. The 43 revised full papers were carefully reviewed and selected from 65 submissions. The papers cover a broad range of topics in combinatorial optimization and applications focussing on experimental and applied research of general algorithmic interest and research motivated by real-world problems.